KONSTRUKSI DAN KONTESTASI DONGENG BERNALAR MORAL ANTI KEKERASAN UNTUK ANAK USIA DINI - Marwany Marwany (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Fairy tale is an effective communication media between children with parents and teachers. Through communication mediated by fairy tale, children get entertainment that gives understanding. Understanding through thinking activities in absorbing values, including the value of anti-violence in language and content of it. For this reason, by carrying out the anti-violence fairy-tale construction of language aspects , means of storytelling, and value, so it will forming the moral reasoning of anti-violence of early childhood. This moral reasoning will then be expressed through children's daily actions. To be able to convey the story of anti-violence effectively in early childhood, the process of fairytale contestation must be done through oral and reading books that are done intensively in the family room by parents, in the school room by the teacher, and in the social space by storytellers. Keywords: Nalar Moral, Dongeng, Anti Kekerasan, dan Anak Usia Dini.